Politeness As a Discursive Practice in The Film Dear John a Critical Discourse Analysis: English - Elita Modesta Sembiring; Jumino Suhadi; Devi Pratiwy (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2026)
Politeness is not merely a pragmatic strategy in interpersonal communication but also a discursive practice shaped by power relations, ideology, and social context. This study examines politeness as a discursive practice in the film “Dear John” (2010) using a Critical Discourse Analysis (CDA) framework. The goal of the study is to reveal how politeness strategies are constructed, negotiated, and contested through language in intimate relationships portrayed in the film. Employing a qualitative descriptive method, the data consist of selected dialogues between the main characters, John and Savannah, which contain politeness-related expressions. The analysis integrates Brown and Levinson’s politeness theory with Fairclough’s three-dimensional model of CDA: textual analysis, discursive practice, and social practice. The findings show that politeness strategies in “Dear John” function not only to maintain interpersonal harmony but also to reflect unequal emotional power, moral positioning, and ideological assumptions about love, sacrifice, and gender roles. Positive politeness dominates the interactions, while negative politeness and off-record strategies emerge in moments of conflict and emotional distance. The novelty of this study lies in its integration of politeness theory and CDA to demonstrate how politeness operates as an ideological and discursive resource within romantic narratives. This study contributes to discourse studies, pragmatics, and literary discourse analysis.